Occupational Health Nurses’ Role in the COVID-19 Pandemic: A literature review (Research, Society and Development, 2024)
The COVID-19 pandemic has imposed unprecedented challenges on health systems worldwide, requiring health professionals to adapt quickly. In this context, occupational health nurses have emerged as key players in ensuring the health and safety of workers, working on several fronts. This article aims to present an overview of the work of occupational health nurses during the COVID-19 pandemic, highlighting their main activities, challenges, and contributions. The literature review revealed that occupational health nurses played a crucial role in preventing and controlling the spread of the virus in the workplace, through the implementation of biosafety measures, epidemiological surveillance, screening of suspected cases, health promotion, and psychosocial support for workers. However, the pandemic has also highlighted challenges such as work overload, shortage of personal protective equipment (PPE), and the need to adapt quickly to new guidelines. Results: Despite the difficulties, occupational health nurses demonstrated great resilience and commitment to workers' health, contributing significantly to tackling the pandemic.